TECHNOLOGY OF BOVINE LEUKEMIA VIRUS GENODIAGNOSTICS IN CATTLE, IN PRODUCED RAW MATERIALS AND PRODUCTS - R. R. Vafin,; Kh. Kh. Gilmanov,; A. G. Galstyan,; N. S. Pryanichnikova,; A. V. Bigaeva,; E. G. Lazareva,; V. S. Kazakova, (Academic Scientific Journal of Chemistry, 2021)
The most important task of the dairy cattle industry is to obtain high quality raw milk. To achieve it, a set of measures is required, including aimed at increasing the biological safety of produced raw materials. The aim of the study was to create a scientific and methodological basis for the Bovine leukemia virus (BLV) gene diagnostics in a combined format of pathogen indication and identification. This required updating the strategy of BLV PCR-RFLP genotyping, consistent with its phylogenetic classification, taking into account the growing knowledge about the genetic diversity of 11 genotypes of the studied viral pathogen. When staging nested PCR, oligonucleotide primers were used, which initiate at the final stage of the reaction the production of a 444 bp env-gene fragment of the pathogen. Five restriction endonucleases were used in PCR-RFLP BLV genotyping of: PvuII, SspI, AsuHPI, HaeIII, and BstX2I. As a result of verification of the developed Bovine leukemia virus method for gene identification with an updated genotyping strategy, a technical result was obtained, expressed in the ability to identify all 11 BLV genotypes discovered to date by interpreting the generated 58 genotype-associated combinations of PCR-RFLP profiles